1981
DOI: 10.1288/00005537-198102000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic salivary tissue and branchial cleft sinus

Abstract: Bilateral lesions which appeared clinically to be branchial cleft sinuses were removed from a patient's neck. One was indeed a branchial cleft sinus, with elements of salivary tissue, but the other proved to be pure salivary tissue with a duct characteristic of a salivary gland. The embryology and clinical characteristics of heterotopic salivary glands are discussed. The occurrence of a heterotopic gland together with a branchial cleft sinus supports the contention that the heterotopic glands arise through err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…One patient did have a contralateral branchial cleft cyst also containing salivary rests. A similar case in which simple HSGT was associated with a contralateral branchial cleft sinus containing salivary tissue has been reported by Goodman et al 15 The association of these anomalies supports the interrelated embryogenesis of these two lesions. 5,15 However, association with other additional congenital anomalies is rare.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One patient did have a contralateral branchial cleft cyst also containing salivary rests. A similar case in which simple HSGT was associated with a contralateral branchial cleft sinus containing salivary tissue has been reported by Goodman et al 15 The association of these anomalies supports the interrelated embryogenesis of these two lesions. 5,15 However, association with other additional congenital anomalies is rare.…”
Section: Discussionsupporting
confidence: 82%
“…A similar case in which simple HSGT was associated with a contralateral branchial cleft sinus containing salivary tissue has been reported by Goodman et al 15 The association of these anomalies supports the interrelated embryogenesis of these two lesions. 5,15 However, association with other additional congenital anomalies is rare. 3 The relationship between HSGT and salivary rests occurring within branchial cleft anomalies, which are known to differentiate into various tissues, remains controversial.…”
Section: Discussionsupporting
confidence: 82%
“…This finding suggests a possible association between HSGT and branchial cleft sinus. In fact, Takimoto and Kato [4] described branchial cleft fistula including salivary gland tissue, and Goodman et al [5] reported a case with the combination of left-sided branchial cleft sinus and right-sided HSGT. However, the sinus from HSGT usually has a shorter length and therefore requires less extensive surgery for removal [6].…”
Section: Discussionmentioning
confidence: 99%
“…tonsil, mandible, lower neck, hypopharynx, sternoclavicular joint or middle ear) [1], To our knowledge, only 23 cases of het erotopic salivary gland tissue in the neck have been reported up to 1986 [2,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%